Needs Analysis for a Psychoeducational Guidance Module Based on Coping Strategies to Enhance the Resilience of Children in Orphanages - Rafli Ramadan; Farida Aryani; Aswar Aswar; Sinta Nurul Oktaviana Kasim (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Resilience is an essential ability that enables children to survive, adapt, and recover from life challenges. However, children living in orphanages often demonstrate low levels of resilience due to experiences of loss, limited emotional support, and the absence of structured psychological guidance. This study aimed to analyze the needs for developing a psychoeducational guidance module based on coping strategies to improve the resilience of orphanage children. The research employed a descriptive qualitative approach using a needs assessment design. The participants were caregivers of Mega Mulia Orphanage in Takalar Regency, selected purposively due to their direct involvement in child guidance. Data were collected through in-depth interviews, and analyzed using data reduction, data display, and conclusion drawing with triangulation techniques to ensure validity. The findings revealed that the main problems experienced by orphanage children included difficulties in emotional regulation, low self-confidence, and inadequate adaptive coping strategies. Existing guidance activities were conducted incidentally and lacked systematic guidelines. These results indicate an urgent need to develop a psychoeducational guidance module based on coping strategies as a structured, practical, and sustainable intervention to support the development of resilience among orphanage children.